Detecting spatial clusters of Crimean Congo hemorrhagic fever in Iraq in 2023 - Hanan Abdulghafoor Khaleel; Riyadh Abdulameer Alhilfi; Sabrina Brown (Global Epidemiology)
Background: Since the start of the first large outbreak of Crimean Congo Hemorrhagic Fever (CCHF) in Iraq in 2022, there has been no assessment of clustering of cases by district. The aim of this study is to identify clusters of high and low incidences of human CCHF to guide preventive and control measures, and distribute limited resources. Methods: This is a cross-sectional study of reported and confirmed CCHF cases in Iraq from January 1, 2023 to December 11, 2023. We used a retrospective purely spatial Poisson scan statistic model to identify clusters of high and low incidences of CCHF at the district level (p < 0.05). Findings: There were 580 confirmed CCHF cases, distributed in 149 districts. The incidence was 1.3 per 100,000. There were eight statistically significant clusters (three high-incidence and five low-incidence). The three high-incidence clusters were in the southeast while the five low-incidence clusters were mostly in the north and middle-east Iraq. Interpretation: There is evidence of CCHF clustering in 40 districts in six governorates in south and mid-east Iraq. Additionally, there is evidence of low-incidence clustering of CCHF in 17 governorates, in north and central Iraq, and a risk for future outbreaks. Identifying clusters allows for focused preventive activities, such as insecticide spraying to reduce the tick population, controlling the spread of ticks by treating animals with repellents and other chemicals, and modifying landscapes. Distributing educational materials about handling meat and livestock products and engaging the community can help reduce exposure to ticks and the spread of disease.